Implementasi Konsep Perbuatan Baik dan Buruk di MA Al Azhar Citangkolo - Hisam Ahyani; Ahmad Hapidin; Andewi Suhartini; Mahmud Mahmud (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2022)
From the discussion above, related to the analysis of the Application of Good and Bad Deeds in MA Al Azhar Citangkolo carried out by the school in learning activities. Where the application of ethics and morals in everyday life is embodied in a disciplined attitude that is applied jointly to students, teachers, and employees, as well as all school stakeholders at MA Al Azhar Citangkolo Banjar City. The strategy in implementing moral education in developing character education at MA Al Azhar Banjar City is carried out in class. Evaluation of the results and process of implementing moral education in the development of character education at MA Al Azhar Banjar City, that evaluation of the implementation of moral education at the end of the semester and also every day in students' daily lives. Qualitative research methods, with a descriptive analytical approach the author uses in this study.